2012
DOI: 10.1515/htmp-2012-0102
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Phenomena in Fe-TiC Systems and the Effect of Cr and Ni

Abstract: Titanium carbide is used as reinforcement com ponent in composites due to its stability, hardness and wear resistance. A potential application is local reinforce ment of stainless steel castings in which TiC is added only to the surfaces, which acquire wear resistance. This work is part of the study in which Ti and C are added in the mould during casting of stainless steel to form TiC at a specific surface. Wettability, stability and dissolution of the reinforcement particles are key phenomena in produc ing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Трещина, доходя до твердого зерна, стремится обогнуть или разрушить его, снижая энергию. Огибая волокна в составе композиционного кермета, трещина увеличивает свой путь, что повышает (по сравнению с керамометаллическими материалами [7,[13][14][15][16][17][18][19]) уровень вязкости разрушения; К Ic = (8,2±0,2) МПа•м 1/2 для материала состава 80 об. % TiC + 10 об.…”
Section: íàó×íûå èññëåäîâàíèß è ðàçðàáîòêèunclassified
“…Трещина, доходя до твердого зерна, стремится обогнуть или разрушить его, снижая энергию. Огибая волокна в составе композиционного кермета, трещина увеличивает свой путь, что повышает (по сравнению с керамометаллическими материалами [7,[13][14][15][16][17][18][19]) уровень вязкости разрушения; К Ic = (8,2±0,2) МПа•м 1/2 для материала состава 80 об. % TiC + 10 об.…”
Section: íàó×íûå èññëåäîâàíèß è ðàçðàáîòêèunclassified
“…In addition, the element carbon diffuses from the TiC into the matrix, which is accompanied by a locally decrease of the solidus temperature and a higher content of liquid phase. It has been observed that TiC can be infiltrated and dissolved through the grain boundaries by the liquid phase [15,16]. However, the (Ti,Mo)C/metal matrix interface is thermodynamically stable and not dissolved by the liquid phase.…”
Section: Diffusion Reactions At the Interface Metal Matrix / Ticmentioning
confidence: 99%
“…Manufacturing technology consists of the smelting of matrix metal in an open-type induction furnace (without protective atmosphere), its further casting into the installation of centrifugal casting of horizontal type with simultaneous supply of tungsten carbide into the metal. As the matrix metal was chosen to mark CSN 14341 [11], since the content of such elements as chromium and nickel in the steel composition increases the performance and the degree of interaction of the refractory particles with metal melts [12,13].…”
Section: Introductionmentioning
confidence: 99%